Resistensi Aedes aegypti terhadap Insektisida Golongan Organofosfat - Suri Dwi Lesmana (Jurnal Ilmu Kedokteran, 2010)
Dengue haemorrhagic fever (DHF) is one of Indonesian public health problems because of its high incidence rate.DHF control is emphasized on vector control Aedes aegypti by using insecticide. Organophosphate has been used asinsecticides to control the dengue vectors for more than 25 years ago. The using of insecticide in long time andsublethal dose can induce insecticide resistance. Aedes aegypti resistance of organophophate have occured based onfisiologic and genetical mechanisms. The major mechanism of resistance to organophosphate insecticides in Aedesaegypti is genetical mechanism. The two major forms of genetical resistance are target site resistance which occurswhen the insecticide no longer binds to its target and detoxification enzyme based resistance through highly activenon specific esterase enzyme.